Marian Wesoły’s Greek Philosophy in Byzantium - Jaworska-Wołoszyn, Magdalena (Peitho. Examina Antiqua, 2017)
Marian Wesoły devoted a considerable part of his life and research to studying the philosophical thought of antiquity. He is, therefore, widely known to scientific community as an admirer of Hellas, outstanding scholar and expert on ancient philosophy, which is reflected in his many publications in the field. Importantly, however, Marian Wesoły, has also been a pioneer of research into a much lesser known field of research, namely Greek philosophy in Byzantium. While this neglected and often disdained area of research has been the subject of Marian Wesoły’s numerous publications, this article presents an over view of his most important findings.